The invention of society : psychological explanations for social phenomena - Moscovici, Serge; Halls, W. D. (Cambridge, UK ; Cambridge, MA : Polity Press, 1993)
Religion and nature as the origins of society. The power of the idea. One of the greatest mysteries in the world.
Keywords: Psychology; Sociology; Sociology; Social psychology